The West African dwarf goat : body size, udder and teat cicumference in relation to kid mortality - Osuagwuh, A.I.A.; Inwang, U.D. (Revue d’élevage et de médecine vétérinaire des pays tropicaux, 1987)
Vaya al archivo pdf del artículo.